Mesenchymal “stem” cells, or facilitators for the development of regenerative macrophages? Pericytes at the interface of wound healing - Marson, Renan Fava; Regner, Andrea Pereira; da Silva Meirelles, Lindolfo (Frontiers in Cell and Developmental Biology, 2023)
Cultured mesenchymal stromal cells (MSCs) are among the most used cells in clinical trials. Currently, their potential benefits include provision of mature cell types through differentiation, and secretion of various types of paracrine signaling molecules. Even though research on these cells has spanned some decades now, surprisingly, their therapeutic potential has not been fully translated into clinical practice yet, which calls for further understanding of their intrinsic nature and modes of action. In this review, after discussing pieces of evidence that suggest that some perivascular cells may exhibit mesenchymal stem cell characteristics in vivo, we examine the possibility that subpopulations of perivascular and/or adventitial cells activated after tissue injury behave as MSCs and contribute to the resolution of tissue injury by providing cues for the development of regenerative macrophages at injured sites. Under this perspective, an important contribution of cultured MSCs (or their acellular products, such as extracellular vesicles) used in cell therapies would be to instigate the development of M2-like macrophages that support the tissue repair process.